2020
DOI: 10.18203/2320-6012.ijrms20203665
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, characteristics, pattern and management of ovarian cancer in Abuja, Nigeria

Abstract: Background: The prevalence of ovarian cancer is thought to be increasing with huge burden of the disease with no comprehensive cancer center that can offer appropriate care in developing countries. However, little is known about the incidence, pattern and outcome of this disease in Abuja, Nigeria. Therefore, the aim of this study was to review the pattern of care offered to patients with ovarian cancer in our center and to evaluate patients’ outcome.Methods: This was a retrospective review of all the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
(60 reference statements)
1
3
0
Order By: Relevance
“…The top three symptoms among patients from our study were abdominal swelling, abdominal pain, and weight loss. These are features of the advanced disease and similar presentations were seen in other studies (11,12,20). Patients with ovarian cancer hardly seek medical assistance early because symptoms are usually non-specific and will only present when the disease has become obvious and unbearable.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The top three symptoms among patients from our study were abdominal swelling, abdominal pain, and weight loss. These are features of the advanced disease and similar presentations were seen in other studies (11,12,20). Patients with ovarian cancer hardly seek medical assistance early because symptoms are usually non-specific and will only present when the disease has become obvious and unbearable.…”
Section: Discussionsupporting
confidence: 76%
“…In a report from FIGO, ovarian cancer was seen more commonly among the age group of 60-64 years in developed countries, and the median age was about a decade earlier in low-income countries (6), which is consistent with what was found in this study. Other studies having similar mean ages include that which was carried out in Abuja (50.2±8.5 years), Kano (50.5 ± 13.5 years), and Kenya 49.8±15.7 years (11,18,19). Nulliparity has been known to be a strong risk factor for ovarian cancer (6,20), however, findings from this study showed a high incidence of ovarian cancer among parous women with a substantial contribution from multiparous women with a median parity (IQR) of 3(0-5).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations